Consumer Perception towards Genetically Modified Products: A Study in Vavuniya - Selvarajan, P.; Weerasinghe, K.P.W.D.R. (Rajarata University of Sri Lanka, 2018)
This study aimed to investigate the consumer perception towards genetically modified products. Genetic modification is a specified set of gene-technology that alters the genetic machinery of living organisms such as animals, plants and microorganisms. Nowadays the genetically modified products are widely available in the market and the consumers have different perception towards those products. Combining genes from different organisms is known as recombinant DNA technology and the resulting is called as genetically modified, genetically engineered or transgenic. Literature prove that the main transgenic crops grown commercially in field are herbicide and insecticide resistant soybeans, corn and canola. In Asian countries numerous number of plant varieties are able to survive in weather extremes. The objectives of this study were to examine the awareness of consumers in Vavuniya town area about these products, their views on these products and whether they have a positive or negative perception towards them.A purposive sampling methodology was used in selecting 100 consumers to the sample. The sample consists of 50 educated employed people and 50 less educated, self employed and unemployed people. A qualitative research approach based on cross-sectional study of ethnography was carried out and the data were gathered through the personal and focused group interviews. The result shows that both the educated and the less educated people have the similar negative perception towards the genetically modified products. However the reasons are somewhat different. Educated people have awareness about these products through their educational knowledge and learning. In contrast, the less educated people have the knowledge through word of mouth and their conservative behaviour. Most of the consumers are aware of the genetically modified plants especially the fruits and vegetables. However, very few people are aware about the genetically modified meat and rice. Therefore, the relevant authorities should take necessary actions to monitor the marketing by making people aware of these products in order to maintain food safety in the country.
Keywords: Consumer Perception; Genetically Modified Products